Self Efficacy Mahasiswa Bimbingan dan Konseling - Khairul Bariyyah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2013)
Self-efficacy is a strong factor in determining a person to act, think and react when faced with situations that are not fun. Students with high self-efficacy tend to have persistent effort, diligent, tenacious and persevering. This research use descriptive- quantitative methodology to indentify level of self efficacy of counseling students specifically will be identified by gender, and ethnicity. This research will identify self efficacy based on differences of gender, and ethnicity. This research use random and purposive random sampling of 45 counseling students from University. These studies identify of self efficacy 31, 1% in low, 66, 7% medium and 2,2 in high condition. Further, there is no significant difference in the level of self efficacy based on gender, and the ethnicity.